A 5-year follow-up case of multiple intrusive luxative injuries - Seema Thakur; Narbir S Thakur (Dental Hypotheses, 2012)
Introduction: Traumatic intrusive luxation is one of the most severe forms of dental injuries, usually affecting the maxillary incisors. The consequence of such an occurrence is a high risk of healing complications such as pulp necrosis, external inflammatory resorption, and external replacement resorption (ankylosis). Case Report: This report presents a case of severe intrusive luxation of multiple anterior teeth in an 11-year-old girl. The teeth were repositioned successfully by endodontic and orthodontic management. The case was monitored for 5 years. Discussion: Depending on the severity of the injury, different clinical approaches for treatment of intrusive luxation may be used. Despite the variety of treatment modalities, rehabilitation of intruded teeth is always a challenge and a multidisciplinary approach is important to achieve a successful result. In this case, intruded teeth were endodontically treated with multiple calcium hydroxide dressings and repositioned orthodontically. The follow-up of such cases is very important as the repair process after intrusion is complex. After 5 years, no clinical or radiographic pathology was detected.